2014
DOI: 10.1016/j.urolonc.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

FASL polymorphism is associated with response to bacillus Calmette-Guérin immunotherapy in bladder cancer

Abstract: FAS-670A/G polymorphism analysis did not reveal any association with BCG therapy outcome. Conclusions:Our results suggest that analysis of FASL-844T/C , but not FAS-670A/G polymorphisms, may be used as a predictive marker of response to BCG immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
3
12
0
1
Order By: Relevance
“…The S1 Table shows the manufacturer references for each evaluated genes. The thermal cycling conditions comprised an initial denaturation step at 95°C for 30 s, 40 cycles at 95°C for 5 s, a 34 s period at 65°C, and a final dissociation stage at 95°C for 15 s, 60°C for 1 min, and 95°C for 15 s [33]. All experiments were performed in duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…The S1 Table shows the manufacturer references for each evaluated genes. The thermal cycling conditions comprised an initial denaturation step at 95°C for 30 s, 40 cycles at 95°C for 5 s, a 34 s period at 65°C, and a final dissociation stage at 95°C for 15 s, 60°C for 1 min, and 95°C for 15 s [33]. All experiments were performed in duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…Deregulation of the FAS/FASL system may lead to immune escape of tumor cells, thereby influencing BCG immunotherapy outcomes [28]. Lima et al demonstrated that carriers of the FASL-844 C/C genotype presented an increased risk of BCG treatment failure and a decreased RFS after BCG treatment when compared with FASL-844 T allele carriers (HR: 1.92, p = 0.03) [29]. This result was able to be validated in an independent study (HR: 1.71, p = 0.04) [6].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In addition, efforts should continue to be devoted towards a more comprehensive and integrated understanding of bladder cancer pathways, the tumor microenvironment and cancer-associated immune responses and their influence in treatment response. Namely, future it would be important to ponder possible factors modulating targetmolecules expression and response profile to immunotherapy, such as the highly variable mutational spectrum of bladder cancers [19,180] and inter-patients variability, as translated by our most recent works in the field of pharmacogenetics [181][182][183]. The tumor microenvironment, in particular the immune responses occurring in stroma [184], is another critical aspect that as remained mostly disregarded and warrants careful investigation in the future.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%